STUDENTS’ PERCEPTION ON THE LECTURER’S FEEDBACK OF THEIR SPEAKING ABILITY IN ONLINE CLASS - Septyana Dwi Utami; Dyah Kusumastuti (Universitas Galuh, 2022)
Speaking English has challenges for each individual to do. Because of the difficulties, the students need feedback from the lecturer in correcting their mistakes in speaking. This research is aimed to find out students’ perception of the lecturer’s feedback on their speaking ability. The research belongs to the descriptive quantitative method which is analyzed someone’s opinion about a thing. The methods of collecting data used in this research were questionnaire and interview. The researchers used the interview to enrich the research data therefore the data sources were trusted. The data from the questionnaire were analyzed using the Likert Scale and determining the mean score of each statement. The sampling technique used in this research was simple random sampling. The samples of the research were 35 students of the English Education Department in a private university in Purwokerto. In addition, the interview data were analyzed using data reduction, data display, and conclusion drawing/reduction. Based on the research that has been conducted, the result of the research was the students have a positive perception of the lecturer’s feedback on the students’ speaking ability. It can be seen in the grand mean score of 3.65, which means this research has a positive perception. From the interview, this research also proves that the lecturer’s feedback is important for the students because it helps the students in correcting their mistakes in practicing speaking English.